Sing you home [compact disc, unabridged] : a novel - Picoult, Jodi, 1966- (Recorded Books, 2011)
Max and Zoe's marriage, stressed by infertility problems and miscarriages, is finally destroyed by a stillborn baby. After their divorce, Max moves in with his brother and sister-in-law, Reid and Liddy, and backslides into self-destructive drinking, while Zoe devotes herself to music therapy that turns into love and marriage. Max, meanwhile, converts to an evangelical brand of Christianity that pits him against Zoe when she asks Max for permission to use their frozen embryos.